Seismic reservoir characterization of deep carbonates under complex overburden: a lithofacies-association zonation workflow, Longwangmiao Formation, Sichuan Basin - Lei Tan; Yuanzhi Zhou; Junliang Li; Linzhi Zhang; Ya Zhang; Pingchao Fang; Minzhi Zhang; Bowen Liu; Longyan Yin; Lin Qiao; Mingzhi Kuang; Hong Liu (Carbonates and Evaporites, 2026)

Mechanisms underlying the impacts of antibiotics on soil microbes and enzyme activities in urban green spaces - Jingfang Li; Liang Chen; Zhibin Jia; Fawen Li (Applied Soil Ecology, 2026)

Crop rotation between vine rows alters soil microbial communities and their associations with grape fruit quality - Qi Xie; Jiawen Liu; Yue Wen; Yulin Fang; Yanlun Ju (Applied Soil Ecology, 2026)

Characteristics of an NDM-1-producing Klebsiella pneumoniae strain belonging to ST105 - Wen Li; Yutong Liu; Yaxu Len; Li Xiang; Caixia Xin; Renjing Hu; Alberto J. Martín-Rodríguez; Bangqiong Weng; Yingshun Zhou (Antonie van Leeuwenhoek, 2026)

Targeting Eustachian Tube Microenvironment: Probiotic Surfactant Utilization for Antimicrobial Peptide Secretion to Prevent Otitis Media - Xichu Duan; Yuning Xing; Wenwen Liu; Li Li (Probiotics and Antimicrobial Proteins, 2026)

IDO1 Inhibitor RY103 Prevents Sepsis-Associated Immunosuppression in Cecal Ligation and Puncture Mice - Zhiyao Li; Mengyuan Fang; Yu Wang; Yunqiu Chen; Yuying Liu; Yijia Chen; Xuewen Li; Fangzhou Meng; Xiaoyang Qian; Zhen Ning Tony He; Qing Yang (Phenomics, 2026)

Evaporation-induced Marangoni effect reshapes flow-by drying of porous matrix adjacent to a gas-flowing fracture - Yandong Zhang; Fei Yu; Shuai Zheng; Bowen Ling; Dongxiao Zhang; Ke Xu (Advances in Water Resources, 2026)

Fungal-driven carbon sequestration within soil aggregates under paddy multicropping - Wei Zhang; Wen Liu; Leyan Zhang; Mengyao Zhou; Rui Xiong; Hongling Qin; Anlei Chen; Baoli Zhu; Zhiqiang Fu; Pan Long (Applied Soil Ecology, 2026)

Freeze-thaw damaged soil microbes but also triggered anti-stress recovery with more abundant functional genes and CO2 emissions - Huinan Ma; Yaxian Hu; Chongzheng Ye; Xianwen Li; Xiaorong Wei (Applied Soil Ecology, 2026)

A hybrid deep learning-data assimilation approach for joint inversion of groundwater contaminant sources and hydraulic conductivity with uncertain boundary conditions - Xuemin Xia; Yule Zhao; Simin Jiang; Yao Hu; Xianwen Li (Advances in Water Resources, 2026)

Rhizospheric bacterial communities and growth-promoting bacteria functional verification in the reclaimed vineyards of Ningxia in Northwest China - Tingting Xue; Xinru Zhao; Shakeel Ahmad; Jiawen Liu; Zhipeng Zhao; Lingxiao Cao; Peiwen Gu; Liang Zhang (Applied Soil Ecology, 2026)

Disease-induced changes in Ganoderma lucidum microbiome co-occurrence patterns and assembly processes - Zhixiang Han; Wenkang Yan; Yujian Yang; Antonino Malacrinò; Xingyue Wang; Weiwen Li; Zhen Zhang; Hongmiao Wu (Applied Soil Ecology, 2026)

Fatty Acid Oxidation Metabolites in Aquatic Animals: Metabolic Pathway, Dynamic Remodeling, and Functional Implications - Zengqi Zhao; Baolin Li; Shunlang Wen; Jianlong Du; Xiuwen Li; Bingyuan Yang; Kangsen Mai; Qinghui Ai (Reviews in Aquaculture, 2026)
As fundamental components of metabolic networks, metabolites act as both energy carriers and signaling molecules, orchestrating a wide range of physiological functions. Consequently, the abundance of metabolites within tissues and cells is typically under tight regulation, with any perturbation of this metabolic equilibrium frequently triggering diverse stress responses and diseases. Recent studies demonstrated that nutritional, environmental, and pathogenic stimuli factors during aquaculture may lead to the remodeling of the fatty acid oxidation pathway in aquatic animals, altering the abundance of fatty acid oxidation‐related metabolites and subsequently triggering stress response cascades. Thus, elucidating the functional roles and regulatory mechanisms of these metabolites is critical for developing targeted strategies to mitigate these stress responses. However, the current progress of research on metabolites related to fatty acid oxidation in aquatic animals is not well summarized. Therefore, in this study, we characterize the fundamental pathways of fatty acid oxidation in aquatic animals and summarize the mechanisms by which these metabolic pathways respond to diverse aquaculture‐related stressors. Furthermore, we systematically elucidate the mechanisms through which these metabolites mediate their regulatory functions, highlighting the distinct physiological roles of the key metabolites. Additionally, we provide our perspectives on the potential applications and future research priorities of fatty acid oxidation‐related metabolites in aquaculture. This review contributes to a better understanding of the dynamics and functions of fatty acid oxidation‐related metabolites in aquatic animals and will facilitate the development of metabolites‐based therapeutic strategies, thereby increasing the sustainability of aquaculture.

Partial wool organic fertilizer substitution mitigate ammonia and nitrous oxide emissions and facilitate savoy cabbage growth - Jiahui Wang; Cun Sun; Shuyan Li; Yixun Shi; Hui Li; Jingchen Song; Jing Yuan; Wenhai Luo; Guoxue Li; Wen Liu; Guoxiang Bu; Hongbin Wang; et al. (Applied Soil Ecology, 2025)

Synergistic effects of PGPR and organic fertilizer on soil fertility, enzyme activities, and microbial community composition in saline-alkali rice systems - Mingfeng Guo; Junzhu Gao; Man Yang; Yawen Liu; Jiahui Fu; Rui Ma; Feng Xiong; Tingyu Zhang; Xuesheng Liu; Yu Jin; Juanjuan Qu (Applied Soil Ecology, 2025)

Mechanisms of lime-induced N2O mitigation in acidic soils: A meta-analysis of microbial activity and substrate dynamics - Kiya Adare Tadesse; Tianfu Han; Zhe Shen; Nano Alemu Daba; Jiwen Li; Muhammad Numan Khan; Asad Shah; Huimin Zhang (Applied Soil Ecology, 2025)

Urban forest soil properties and microbial characteristics: seasonal and stand-specific variations - Xin Wan; Sumei Qiu; Runyang Zhou; Liwen Li; Wei Xing; Yingdan Yuan (Applied Soil Ecology, 2025)

Differential response of soil abundant and rare bacterial subcommunities in the natural restoration process of oil well sites in the Loess Plateau - Yanan Wang; Jian Deng; Ziyue Chen; Yunhuan Jia; Dan Zhang; Jiangwen Li; Xiaoxi Zhang (Applied Soil Ecology, 2024)

Recovery of bacterial network complexity and stability after simulated extreme rainfall is mediated by K−/r-strategy dominance - Yin Wang; Mengjun Qu; Jianming Wang; Weilin Zhu; Jingwen Li (Applied Soil Ecology, 2024)

Enforcing global constraints for the dispersion closure problem: τ 2 -SIMPLE algorithm - Ross M. Weber; Bowen Ling; Ilenia Battiato (Advances in Water Resources, 2024)

Decreasing elevational gradient in peak photosynthesis timing on the Tibetan Plateau - Yongwen Liu; Jinzhi Ding; Peilin Li; Rongrong Zhang; Jingxue Zhao; Tsechoe Dorji (Agricultural and Forest Meteorology, 2023)

Construction of a spatially gridded heat flux map based on airborne flux Measurements using remote sensing and machine learning methods - Yibo Sun; Li Jia; Qiting Chen; Xingwen Lin; Bilige Sude; Zhanjun Quan; Ronald W.A. Hutjes (Agricultural and Forest Meteorology, 2023)

Biomanipulation-induced reduction of sediment phosphorus release in a tropical shallow lake - Xiufeng Zhang; Yali Tang; Erik Jeppesen; Zhengwen Liu (Hydrobiologia, 2017)

Submerged macrophytes facilitate dominance of omnivorous fish in a subtropical shallow lake: implications for lake restoration - Jinlei Yu; Zhengwen Liu; Hu He; Wei Zhen; Baohua Guan; Feizhou Chen; Kuanyi Li; Ping Zhong; Franco Teixeira-de Mello; Erik Jeppesen (Hydrobiologia, 2016)

Size-dependent feeding of omnivorous Nile tilapia in a macrophyte-dominated lake: implications for lake management - Weimin Rao; Jiajia Ning; Ping Zhong; Erik Jeppesen; Zhengwen Liu (Hydrobiologia, 2015)

Nitrogen inputs enhance phytoplankton growth during sediment resuspension events: a mesocosm study - Hu He; Yuhui Kang; Zhengwen Liu (Hydrobiologia, 2015)

Cyanobacterial carbon supports the growth and reproduction of Daphnia: an experimental study - Xiaoxia Luo; Zhengwen Liu; Ramesh D. Gulati (Hydrobiologia, 2015)

How important are trophic state, macrophyte and fish population effects on cladoceran community? A study in Lake Erhai - Guimin Liu; Zhengwen Liu; Binhe Gu; Joseph M. Smoak; Zhuo Zhang (Hydrobiologia, 2014)

Fish community assemblages changed but biomass remained similar after lake restoration by biomanipulation in a Chinese tropical eutrophic lake - Jian Gao; Zhengwen Liu; Erik Jeppesen (Hydrobiologia, 2014)

Restoration of a subtropical eutrophic shallow lake in China: effects on nutrient concentrations and biological communities - Feizhou Chen; Tingting Shu; Erik Jeppesen; Zhengwen Liu; Yuwei Chen (Hydrobiologia, 2013)